2018
DOI: 10.1002/jcp.27903
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA CASC9 promotes LIN7A expression via miR‐758‐3p to facilitate the malignancy of ovarian cancer

Abstract: The long noncoding RNA cancer susceptibility 9 (CASC9) has been reported to be a pivot modulator in growth and metastasis of breast cancer, liver cancer, esophageal squamous cell carcinoma, lung adenocarcinoma, gastric cancer, and nasopharyngeal cancer. However, its potential roles in ovarian cancer remain unclear. In this study, we aimed at its functions and molecular mechanism in ovarian cancer progression. We showed that CASC9 was highly expressed in ovarian cancer tissues and cell lines. An elevated level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 24 publications
2
51
0
Order By: Relevance
“…As the results show, MAGI1-IT1 was principally localized in the cytoplasm, with weak expression in the nucleus (Figure 4(a)). Since cytoplasmic lncRNAs have the ability to bind to many biomolecules, ceRNAs have emerged as an important mechanism for lncRNAs and miRNAs regulatory networks [26,27]. Thus, the associations among MAGI1-IT 1, corresponding miRNAs and mRNAs were subsequently predicted.…”
Section: Magi1-it1 May Serve As a Cerna Of Mir-200a In Regulating Zebmentioning
confidence: 99%
“…As the results show, MAGI1-IT1 was principally localized in the cytoplasm, with weak expression in the nucleus (Figure 4(a)). Since cytoplasmic lncRNAs have the ability to bind to many biomolecules, ceRNAs have emerged as an important mechanism for lncRNAs and miRNAs regulatory networks [26,27]. Thus, the associations among MAGI1-IT 1, corresponding miRNAs and mRNAs were subsequently predicted.…”
Section: Magi1-it1 May Serve As a Cerna Of Mir-200a In Regulating Zebmentioning
confidence: 99%
“…Moreover, CASC9 has been identified as a tumor promoter in multiple cancers. For instance, CASC9 promotes the development of ovarian cancer by regulating miR-758-3p/LIN7A axis [15]. Attenuation of CASC9 accelerates GC cell apoptosis [16].…”
Section: Introductionmentioning
confidence: 99%
“…These results imply that miR-758 serves as a tumor suppressor in CRC progression. Previous studies have also reported the downregulation of miR-758 in human cancers, such as ovarian and gastric cancer (17,18). Also, miR-758 has been found to inhibit cell migration, invasion and proliferation in bladder cancer, hepatocellular carcinoma and glioblastoma (19)(20)(21).…”
Section: Discussionmentioning
confidence: 92%